A Tangled Tale: Trichobezoar in a Young Patient with Undiagnosed Celiac Disease - Espinal Niki; Lyons Hernando; Langenberg Scott; Kumar Sanjay (AMERICAN JOURNAL OF CASE REPORTS AND CLINICAL IMAGES, 2025)
Trichobezoars are uncommon gastrointestinal masses composed of ingested hair. Celiac disease is an immune-mediated disease triggered by gluten ingestion and can present with a variety of gastrointestinal and extra-gastrointestinal symptoms. We report the case of a 6-year-old girl with a history of trichophagia who was found to have both a large gastric trichobezoar and newly diagnosed celiac disease. This case highlights the significance of how nutritional deficiencies and psychological problems can potentially lead to abnormal eating behaviors resulting in complicated gastrointestinal manifestations. References 1. Naik S, Gupta V, Naik S, Rangole A, Chaudhary AK, Jain P, Sharma AK. Rapunzel syndrome reviewed and redefined. Dig Surg. 2007;24(3):157- 61. doi: 10.1159/000102098. Epub 2007 Apr 27. PMID: 17476105. 2. Vaughn ED, Sawyers JL, Scott HW. The Rapunzel syndrome. Am 1968;115(6):735-738. https://doi.org/10.1016/0002- J Surg. 9610(68)90257-1 3. Husby S, Koletzko S, Korponay-Szabó IR, et al. ESPGHAN guidelines for diagnosing coeliac disease.J Pediatr Gastroenterol Nutr. 2012;54(1):136- 160. https://doi.org/10.1097/MPG.0b013e31821a23d0 4. Guandalini S, Assiri A. Celiac disease: A review. JAMA Pediatr. 2014;168(3):272-278. https://doi.org/10.1001/ jamapediatrics.2013.3858 5. Hill ID, Fasano A, Guandalini S, et al. NASPGHAN guidelines for diagnosis and treatment of celiac disease in children. J Pediatr Gastroenterol Nutr. 2005;40(1):1-19. https://doi.org/10.1097/01. mpg.0000181841.51374.4c 6. Irastorza, I., Tutau, C., & Vitoria, J. C. (2014). A trichobezoar in a child with undiagnosed celiac disease: a case report. World journal of gastroenterology, 20(5), 1357-1360. https://doi.org/10.3748/wjg. v20.15.1357 7. Freeman H. J. (2015). Iron deficiency anemia in celiac disease. World journal of gastroenterology, 21(31), 9233-9238. https://doi. org/10.3748/wjg.v21.131.9233 8. Miao, D., Young, S. L., & Golden, C. D. (2015). A meta-analysis of pica and micronutrient status. American journal of human biology: the official journal of the Human Biology Council, 27(1), 84-93. https://doi. org/10.1002/ajhb.22598 9. Elnaim, A.L.K., Shareef, S.M., Ebrahim, M.A.A. et al. Gastric trichobezoar as first presentation of psychiatric disorders in young women: case series. Discov Med 1, 112 (2024). https://doi.org/10.1007/s44337- 024-00132-5